Examination of self sufficiency beliefs of the physical education and sports academies students towards english lesson - Hakkı Ulucan; Ziya Bahadır; Enes Beltekın (Türk Spor ve Egzersiz Dergisi)
This research was conducted to determine the self sufficiency beliefs of the students study at different departments at Erciyes University and Selcuk University Physical Education and Sports Schools in 2014-2015 Academic year. Totally 511 students, 296 males and 215 females, formed the study group of the research. Datum of the research gathered by Self sufficiency belief scale about English and scale was developed by Yanar amp; Büme. On the gathered datum the Frequency, Percentage, Arithmetic mean, MannWhitney-U test and Kruskal Wallis test were conducted. The significance level between the variables and the difference was considered as 0,05 level. As a result; It has been found that the students' self sufficiency beliefs for English lessons are low (sleep very little). While there was a significant difference coincided in favor of men in the subscale of speech according to gender variable, there were significant differences found in favor of Erciyes University students in Reading, Writing and Listening sub-dimensions according to university variance. While there was no meaningful difference determined according to the department variance that students study at, there was a significant difference determined in favor of those who had the highest academic passing grade according to academic course passing grade variance.